2016
DOI: 10.17140/doj-2-125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Golden Proportion Between Maxillary Anterior Teeth of South Indian Population

Abstract: Golden proportion is a proportion frequently present in nature and is considered as a means of achieving harmony in the teeth. It forms an important aspect of aesthetic dentistry as it deals with the restoration of the maxillary anterior teeth in relation to their widths. Aim: The study was conducted to evaluate the presence of golden proportion between the maxillary anterior teeth in south Indian population by examining their widths. The study also aimed to evaluate the existing ratio present in the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…However, no significant difference between both groups was found. This result is similar to the results of some previous studies conducted in India [14,19,[24][25][26][27][28], Iran [29][30][31], Pakistan [32][33][34], Malaysia [35], Jordan [36], Brazil [37], Romania [38], Nepal [39], China [40], Korea [41], Hungary [42], and in Irish, Iraqi, and Kurdish samples for the canine to lateral ratio [43,44]. However, our results contrast other studies conducted among other Indian [45] and Pakistani [46] samples, which found the golden ratio suitable for esthetic appearance.…”
Section: Discussionsupporting
confidence: 92%
“…However, no significant difference between both groups was found. This result is similar to the results of some previous studies conducted in India [14,19,[24][25][26][27][28], Iran [29][30][31], Pakistan [32][33][34], Malaysia [35], Jordan [36], Brazil [37], Romania [38], Nepal [39], China [40], Korea [41], Hungary [42], and in Irish, Iraqi, and Kurdish samples for the canine to lateral ratio [43,44]. However, our results contrast other studies conducted among other Indian [45] and Pakistani [46] samples, which found the golden ratio suitable for esthetic appearance.…”
Section: Discussionsupporting
confidence: 92%
“…Some other authors have also mentioned the use of this proportion in anterior esthetics [7,8]. On the other hand few studies including a few done on south Asian population have shown that the golden proportion was rarely seen in maxillary anteriors [8][9][10][11].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of golden proportion in the past has been determined for different ethnic groups in different studies. According to Hegde [10] Golden proportion was not prevalent in the south Indian population and did not serve as an adequate guideline to be applied to all maxillary anterior teeth.…”
Section: Golden Proportion In Different Types Of Smile: a Photographimentioning
confidence: 99%
“…Also, Mahajan V. found that GP did not present in most cases of the Himachal Pradesh population in north India. [ 6 ] Similarly, Hegde and Malhotra[ 7 ] found that GP was not prevalent in the south Indian population where the ratio of central incisor and lateral incisor on both sides was 1.23 and 1.18, respectively. Al-marzouk et al [ 8 ] evaluated GP and GS of maxillary central incisors in three different races living in Malaysia.…”
Section: Introductionmentioning
confidence: 99%